2001
DOI: 10.1123/ijsnem.11.3.384
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-Methylbutyrate (HMB) Supplementation Does Not Affect Changes in Strength or Body Composition during Resistance Training in Trained Men

Abstract: This investigation evaluated the effects of oral beta-hydroxy-beta-methylbutyrate (HMB) supplementation on training responses in resistance-trained male athletes who were randomly administered HMB in standard encapsulation (SH), HMB in time release capsule (TRH), or placebo (P) in a double-blind fashion. Subjects ingested 3 g x day(-1) of HMB or placebo for 6 weeks. Tests were conducted pre-supplementation and following 3 and 6 weeks of supplementation. The testing battery assessed body mass, body composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
3
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 0 publications
1
82
3
7
Order By: Relevance
“…These results repeated in Thomson et al 22 study in trained men after 9 weeks resistance training. But these findings are not supported by several investigations 8,9,16,24,27,28 .…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…These results repeated in Thomson et al 22 study in trained men after 9 weeks resistance training. But these findings are not supported by several investigations 8,9,16,24,27,28 .…”
Section: Discussioncontrasting
confidence: 50%
“…It has been suggested that HMB supplementation with 1.5 to 3 g per day reduces muscle proteolysis and increases strength and muscle mass after 3-8 weeks strength training 6,7 . However, these findings aren't confirmed by other studies 8,9 .…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The low effectiveness of HMB in strength‐trained athletes could be due to the suppression of the proteolysis that is induced by the adaptation to training, which may blunt the effects of HMB 51. Other studies suggest that a longer pre‐exercise supplementation period may be necessary 47.…”
Section: Hmb As a Nutritional Supplementmentioning
confidence: 99%
“…Em um estudo randomizado e duplo-cego, Slater et al 34 avaliaram, durante seis semanas, possíveis mudanças em força e composição corporal de atletas de pólo aquático e remo divididos nos grupos placebo e 3,0g de HMB. Todos os sujeitos participaram de um programa de treinamento contra-resistência 2-3 vezes por semana, constando de 3-5 séries com 4-6 repetições.…”
Section: Efeitos Do Hmb Em Indivíduos Treinados Em Atividade Contra-runclassified